Silicon-based rare earth catalyst based on ZMQ-1 molecular sieve

By adopting the composition and process of silicon-based rare earth catalyst based on ZMQ-1 molecular sieve, the problem of carbon accumulation and inactivation in traditional catalysts at high temperatures is solved, and the performance and stability of the catalytic cracking reaction are significantly improved.

CN119897153APending Publication Date: 2025-04-29QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411834658.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Traditional catalytic cracking catalysts are prone to carbon accumulation and inactivated under high temperatures and high loads, and have low conversion rate of light oil.

Method used

A silicon-based rare earth catalyst based on ZMQ-1 molecular sieve is used to form a catalyst that includes 60-80% of ZMQ-1 molecular sieve, 5-15% of rare earth metal, 5-10% of transition metal cocatalyst, and 5-10% of binder. The pore structure and acidic characteristics of the catalyst are optimized through specific synthesis processes and treatment steps.

Benefits of technology

The performance of catalytic cracking reaction is significantly improved, especially in terms of improving conversion rate and light oil selectivity, which extends the service life of the catalyst, reduces the carbon deposit rate, and ensures long-term reaction stability and efficient operation of the catalytic cracking process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897153A_ABST
    Figure CN119897153A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of molecular sieve catalysts, and discloses a ZMQ-1 molecular sieve-based silicon-based rare earth catalyst, which comprises, by weight, 60-80% of a ZMQ-1 molecular sieve, 5-15% of a rare earth metal, 5-10% of a transition metal promoter, and 5-10% of a binder, the rare earth metal is selected from yttrium, neodymium, cerium and a combination thereof, and the transition metal promoter is selected from yttrium, neodymium, cerium and a combination thereof. The transition metal promoter is ammonium molybdate, sodium tungstate and a combination thereof, the crystal structure of the ZMQ-1 molecular sieve is a cubic system, and the ZMQ-1 molecular sieve has a pore structure with a specific surface area of 300-600m < 2 > / g. The rare earth metal and the transition metal are introduced into the ZMQ-1 molecular sieve, so that the acidic characteristic and the carbon deposition resistance of the catalyst are improved, meanwhile, the pH value of a reaction solution, a template agent and hydrothermal reaction conditions are accurately controlled, the pore channel structure of the ZMQ-1 molecular sieve is optimized, and the specific surface area and acidic sites are increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of molecular sieve catalysts, in particular to a silicon-based rare earth catalyst based on a ZMQ-1 molecular sieve. Background Art

[0002] With the consumption of modern fossil energy and the increasing global demand for clean energy, oil cracking technology occupies a vital position in the oil refining industry. As one of the core technologies of oil refining, catalytic cracking technology is widely used to convert heavy oil in crude oil into light oil, gasoline, diesel and other high value-added products. With the growing market demand for light oil and high value-added chemicals, the performance and stability of catalysts in the catalytic cracking reaction process have become important factors restricting the further development of this technology.

[0003] Traditional catalytic cracking catalysts mostly use aluminosilicate molecular sieves, such as ZSM-5, Y-type molecular sieves, etc. Although these catalysts can provide better catalytic performance to a certain extent, they are easily affected by carbon deposition during the catalytic reaction, resulting in reduced catalyst activity and catalytic efficiency, thereby shortening the service life of the catalyst. In order to overcome this problem, researchers have tried to improve the comprehensive performance of the catalyst by modifying the acidic properties, structural stability and anti-carbon deposition performance of the catalyst.

[0004] In recent years, the introduction of rare earth metals has become an important means to improve catalyst performance. Rare earth metals have unique chemical properties that can optimize the acidic characteristics of molecular sieves and improve the thermal stability and carbon deposition resistance of catalysts. However, many current studies are still limited to rare earth metal doping of catalysts through traditional modification methods, failing to give full play to the synergistic effect between rare earth metals and molecular sieve materials, and the pore structure and specific surface area of ​​the catalyst are often not effectively optimized.

[0005] To solve these problems, the present invention provides a silicon-based rare earth catalyst based on ZMQ-1 molecular sieve. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a silicon-based rare earth catalyst based on ZMQ-1 molecular sieve, which solves the problems of carbon deposition and deactivation of traditional catalytic cracking catalysts at high temperature and high load, as well as low light oil conversion rate.

[0007] To achieve the above objectives, the present invention is implemented through the following technical scheme: based on the ZMQ-1 molecular sieve silicon-based rare earth catalyst, it includes the following components by weight percentage: 60-80% ZMQ-1 molecular sieve, 5-15% rare earth metal, 5-10% transition metal promoter, and 5-10% binder.

[0008] Preferably, the rare earth metal is selected from yttrium, neodymium, cerium and combinations thereof.

[0009] Preferably, the transition metal co-catalyst is ammonium molybdate, sodium tungstate and a combination thereof.

[0010] Preferably, the crystal structure of the ZMQ-1 molecular sieve is cubic, with a specific surface area of ​​300-600m 2 / g pore structure.

[0011] Preferably, the preparation process of the catalyst is as follows:

[0012] S1, providing a silicon source, an aluminum source, a rare earth metal source and a transition metal source, and mixing them in the above weight percentage ratio to form a reaction solution;

[0013] S2, adding a template to the reaction solution, adjusting the pH value to 10-12, and reacting under high pressure hydrothermal conditions to obtain a ZMQ-1 molecular sieve;

[0014] S3, adding a rare earth metal source to the obtained ZMQ-1 molecular sieve, and reacting at 60-80° C. to uniformly incorporate the rare earth metal into the molecular sieve framework;

[0015] S4, adding a transition metal source to the reaction solution for impregnation treatment to evenly distribute the transition metal on the surface of the molecular sieve;

[0016] S5. The catalyst is calcined and phosphorylated.

[0017] Preferably, in step S1, the silicon source is silicon tetrachloride, the aluminum source is aluminate, the rare earth metal source is rare earth chloride, specifically yttrium, neodymium or cerium chloride, and the transition metal source is ammonium molybdate or sodium tungstate.

[0018] Preferably, the step S2 specifically includes the following steps:

[0019] S2.1, adding a silicon source and an aluminum source into deionized water, adjusting the pH value of the solution to 10-12, to form a reaction solution;

[0020] S2.2, add template to the solution and keep stirring;

[0021] S2.3, transferring the mixed solution to an autoclave, and performing a hydrothermal reaction at 180-200°C for 12-24h to obtain preliminary ZMQ-1 molecular sieve crystals;

[0022] S2.4. After the reaction is completed, the template is removed by filtration, and the ZMQ-1 molecular sieve matrix is ​​obtained by washing, and then dried to obtain a preliminary molecular sieve material.

[0023] Preferably, the template in step S2.2 is selected from CTAB and PEI.

[0024] Preferably, the specific steps of step S5 are as follows:

[0025] S5.1, the calcination temperature is set to 550-600°C, the calcination time is 6-10h, and the calcination process needs to be carried out under nitrogen or air atmosphere;

[0026] S5.2, immersing the calcined catalyst in a phosphoric acid solution for phosphorylation;

[0027] S5.3. Dry the treated catalyst at 110° C. to obtain the final ZMQ-1 molecular sieve-based silicon-based rare earth catalyst.

[0028] Preferably, the concentration of the phosphoric acid solution in step S5.2 is 0.1-1.0 mol / L.

[0029] The present invention provides a silicon-based rare earth catalyst based on ZMQ-1 molecular sieve, which has the following beneficial effects:

[0030] 1. The present invention significantly optimizes the performance of catalytic cracking reaction by introducing rare earth metals into ZMQ-1 molecular sieve, especially in improving conversion rate and light oil selectivity. Rare earth metals can improve the acidic characteristics of molecular sieves, promote the generation of shorter chain olefins and hydrocarbon compounds, thereby increasing the yield of light oil and reducing the generation of heavy oil. This technology can effectively improve the utilization rate of light oil in the refining process, which meets the demand of modern refining industry for high value-added products.

[0031] 2. The present invention optimizes the carbon deposition resistance of the catalyst by introducing transition metals into the surface of the ZMQ-1 molecular sieve. The transition metals have strong electronic structures and chemical properties, which can effectively reduce the formation of carbon deposition in the catalytic process. Combined with the effect of rare earth metals, the anti-carbon deposition performance of the catalyst is further improved, thereby improving the stability of the catalyst. By adopting a special synthesis process, the catalyst prepared by the present invention maintains a low carbon deposition rate under high temperature and long-term operation, avoids the problem of catalyst deactivation, ensures long-term reaction stability and efficient operation in the catalytic cracking process, reduces the frequency of catalyst replacement, and improves the economy and sustainability of production.

[0032] 3. The present invention optimizes the pore structure of the ZMQ-1 molecular sieve by precisely controlling the pH value of the reaction solution, the type of template, and the hydrothermal reaction conditions, thereby enabling the catalyst to obtain a larger specific surface area, thereby providing more acid sites for the catalytic reaction, improving the reactivity and selectivity of the catalyst, and allowing the reactants to enter the active area of ​​the catalyst more quickly and undergo cracking reactions therein to produce more light oil and olefin compounds. The precise control of the pore structure also improves the durability of the catalyst, making the catalytic reaction more stable and efficient during long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention is a flow chart of the catalyst preparation method. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Please see attached Figure 1 The embodiment of the present invention provides a silicon-based rare earth catalyst based on ZMQ-1 molecular sieve, which includes the following components by weight percentage: 60-80% ZMQ-1 molecular sieve, 5-15% rare earth metal, 5-10% transition metal promoter, and 5-10% binder.

[0036] Specifically, ZMQ-1 molecular sieve, as the basic component of the catalyst, plays a key role in the catalytic cracking reaction. ZMQ-1 molecular sieve has a high specific surface area, excellent pore structure and acid sites, which enable the catalyst to show efficient reaction activity in the cracking reaction. Its cubic crystal structure provides pore characteristics suitable for catalytic reactions, allowing reactants to quickly enter the active area of ​​the catalyst, ensuring effective cracking of reactants and the generation of light oil. In addition, the pore structure and acid sites of ZMQ-1 molecular sieve can effectively promote the generation of olefins and hydrocarbon compounds, thereby improving the selectivity and conversion rate of light oil.

[0037] The introduction of rare earth metals is one of the important innovations of the present invention. Rare earth metals (such as yttrium, neodymium, cerium) have good acidity regulating effects, which can enhance the acidic characteristics of ZMQ-1 molecular sieves and promote the generation of more light oils by improving the density of acid sites on the catalyst surface. The presence of rare earth metals can also effectively improve the anti-carbon deposition performance of the catalyst and prevent the deactivation of the catalyst due to excessive carbon deposition in the reaction. The addition of rare earth metals ensures the high selectivity of the catalyst in the catalytic cracking reaction, especially at high temperatures, and can continuously maintain a high catalytic activity, reducing the frequency of catalyst replacement and improving the economic efficiency of production.

[0038] The addition of transition metal promoters further optimizes the catalyst's resistance to carbon deposition. Transition metals such as molybdenum and tungsten have strong chemical activity and can effectively reduce the formation of carbon deposits in catalytic reactions and extend the service life of the catalyst. They reduce the deposition of carbonized products by adjusting the electronic structure of the catalyst, and synergize with rare earth metals to further improve the stability of the catalyst. Transition metal promoters play a key role in improving the durability and reaction stability of the catalyst, ensuring the high efficiency and reliability of the catalytic cracking process under long-term operation.

[0039] The addition of binders ensures the physical strength and stability of the catalyst. In the high temperature and high pressure catalytic cracking reaction environment, catalyst particles are easily affected by mechanical shock and thermal expansion, resulting in catalyst fragmentation. Binders can enhance the physical strength of the catalyst and prevent the catalyst from breaking or losing activity during the reaction, thereby ensuring its long-term stable operation. In addition, the addition of binders also helps to improve the processability of the catalyst, making the catalyst particles more uniform, ensuring uniform load distribution during the reaction, and improving the reliability of the catalyst.

[0040] The rare earth metal is selected from yttrium, neodymium, cerium and combinations thereof.

[0041] The transition metal promoter is ammonium molybdate, sodium tungstate and a combination thereof.

[0042] The crystal structure of ZMQ-1 molecular sieve is cubic, with a specific surface area of ​​300-600m 2 / g pore structure.

[0043] Specifically, the rare earth metals selected in the present invention include yttrium, neodymium, cerium and combinations thereof. These rare earth metals have good acidity regulating effects and can significantly improve the acidic properties of the catalyst. Rare earth metals further improve the selectivity and conversion rate of light oil in catalytic cracking reactions by enhancing the distribution of acid sites on the surface of molecular sieves, especially in promoting the breaking of C-C bonds and the formation of olefins. The introduction of rare earth metals such as yttrium, neodymium and cerium can enhance the catalyst's anti-carbon deposition performance, slow down the deactivation of the catalyst, improve its high temperature resistance, and ensure that the catalyst can still maintain efficient catalytic activity under high temperature conditions.

[0044] Transition metal promoters such as ammonium molybdate, sodium tungstate and their combination can effectively improve the carbon deposition resistance of the catalyst. The special electronic structure of transition metals can reduce the formation of carbon deposition during catalytic cracking and extend the service life of the catalyst. Transition metals such as molybdenum and tungsten have strong catalytic activity, which can help decompose the heavy oil components in the reaction, and enhance the stability and carbon deposition resistance of the catalyst by synergizing with rare earth metals, thereby ensuring the long-term and efficient operation of the catalytic cracking reaction.

[0045] ZMQ-1 molecular sieve plays an important role in the present invention. Its crystal structure is cubic and has a large specific surface area (300-600m 2 / g) and good pore structure. The large specific surface area can provide more acid sites, increase the contact opportunities between reactants and catalysts, and thus improve the reaction efficiency. The pore structure of ZMQ-1 is precisely controlled, making the catalytic reaction more efficient. Its larger pore size can effectively accommodate and catalyze larger molecules, improve the light oil generation in the catalytic cracking process by adjusting the acid site density, and improve the selectivity of the catalyst.

[0046] The preparation process of the catalyst is as follows:

[0047] S1, providing a silicon source, an aluminum source, a rare earth metal source and a transition metal source, and mixing them in the above weight percentage ratio to form a reaction solution;

[0048] S2, adding a template to the reaction solution, adjusting the pH value to 10-12, and reacting under high pressure hydrothermal conditions to obtain a ZMQ-1 molecular sieve;

[0049] S3, adding a rare earth metal source to the obtained ZMQ-1 molecular sieve, and reacting at 60-80° C. to uniformly incorporate the rare earth metal into the molecular sieve framework;

[0050] S4, adding a transition metal source to the reaction solution for impregnation treatment to evenly distribute the transition metal on the surface of the molecular sieve;

[0051] S5. The catalyst is calcined and phosphorylated.

[0052] In step S1, the silicon source is silicon tetrachloride, the aluminum source is aluminate, the rare earth metal source is rare earth chloride, specifically yttrium, neodymium or cerium chloride, and the transition metal source is ammonium molybdate or sodium tungstate.

[0053] The S2 step specifically includes the following steps:

[0054] S2.1, adding a silicon source and an aluminum source into deionized water, adjusting the pH value of the solution to 10-12, to form a reaction solution;

[0055] S2.2, add template to the solution and keep stirring;

[0056] S2.3, transferring the mixed solution to an autoclave, and performing a hydrothermal reaction at 180-200°C for 12-24h to obtain preliminary ZMQ-1 molecular sieve crystals;

[0057] S2.4. After the reaction is completed, the template is removed by filtration, and the ZMQ-1 molecular sieve matrix is ​​obtained by washing, and then dried to obtain a preliminary molecular sieve material.

[0058] In step S2.2, the template agent can be CTAB or PE I.

[0059] The specific steps of step S5 are as follows:

[0060] S5.1, the calcination temperature is set to 550-600°C, the calcination time is 6-10h, and the calcination process needs to be carried out under nitrogen or air atmosphere;

[0061] S5.2, immersing the calcined catalyst in a phosphoric acid solution for phosphorylation;

[0062] S5.3. Dry the treated catalyst at 110° C. to obtain the final ZMQ-1 molecular sieve-based silicon-based rare earth catalyst.

[0063] The concentration of the phosphoric acid solution in step S5.2 is 0.1-1.0 mol / L.

[0064] Embodiment 1:

[0065] Embodiment 1 Specific steps:

[0066] Raw material preparation: Silicon tetrachloride is selected as the silicon source, aluminate is used as the aluminum source, yttrium chloride is used as the rare earth metal source, and ammonium molybdate is used as the transition metal source. By weight percentage, ZMQ-1 molecular sieve accounts for 70%, yttrium accounts for 10%, ammonium molybdate accounts for 7%, and binder accounts for 8%.

[0067] Preparation of reaction solution: Add silicon source, aluminum source, rare earth metal source and transition metal source into deionized water according to the above proportions, and adjust the pH value to 10.5.

[0068] Hydrothermal synthesis: The hydrothermal reaction was carried out in an autoclave with the temperature controlled at 190°C and the reaction time being 20 h to obtain ZMQ-1 molecular sieve.

[0069] Catalyst impregnation treatment: The obtained ZMQ-1 molecular sieve is added into a rare earth metal source (yttrium chloride) solution, the reaction temperature is controlled at 70°C, and the reaction time is 6 hours, so that the rare earth metal is evenly incorporated into the molecular sieve framework.

[0070] Calcination and phosphorylation: The calcination temperature was set at 550°C for 8 hours in a nitrogen atmosphere. Subsequently, the catalyst was immersed in a 0.5 mol / L phosphoric acid solution for phosphorylation and then dried at 110°C to obtain the final catalyst.

[0071] Summary of Example 1: This example provides a basic method for preparing a ZMQ-1 molecular sieve silicon-based rare earth catalyst. By optimizing the hydrothermal synthesis conditions and rare earth metal incorporation technology, the prepared catalyst exhibits good catalytic performance in conventional catalytic cracking, and has a high specific surface area and a moderate acid site distribution, and is suitable for use in conventional cracking reactions.

[0072] Embodiment 2:

[0073] Embodiment 2 Specific steps:

[0074] Raw material preparation: Silicon tetrachloride is selected as the silicon source, aluminate is used as the aluminum source, the rare earth metal source is a mixture of neodymium chloride and yttrium chloride, and the transition metal source is sodium tungstate. By weight percentage, ZMQ-1 molecular sieve accounts for 65%, the mixture of neodymium and yttrium accounts for 10%, sodium tungstate accounts for 6%, and the binder accounts for 9%.

[0075] Preparation of reaction solution: Add silicon source, aluminum source, rare earth metal source and transition metal source into deionized water according to the above proportions, and adjust the pH value to 11.

[0076] Hydrothermal synthesis: The hydrothermal reaction was carried out in an autoclave with the temperature controlled at 200°C and the reaction time being 24 h to obtain ZMQ-1 molecular sieve.

[0077] Catalyst impregnation treatment: Add the obtained ZMQ-1 molecular sieve into the chloride solution of neodymium and yttrium, control the reaction temperature at 75°C, and the reaction time for 8 hours to uniformly incorporate the rare earth metal into the molecular sieve framework.

[0078] Calcination and phosphorylation: The calcination temperature was set at 580°C for 9 hours in an air atmosphere. Subsequently, the catalyst was immersed in a 0.8 mol / L phosphoric acid solution for phosphorylation and then dried at 120°C to obtain the final catalyst.

[0079] Summary of Example 2: Based on Example 1, Example 2 significantly enhances the high temperature stability and catalytic performance of the catalyst by optimizing the type and doping ratio of rare earth metals and the selection of transition metal promoters. In particular, the use of sodium tungstate improves the stability of the catalyst at high temperatures and makes the catalyst exhibit higher durability during the catalytic cracking process, making it suitable for more demanding reaction conditions.

[0080] Embodiment three:

[0081] Embodiment 3 Specific steps:

[0082] Raw material preparation: Silicon tetrachloride is selected as the silicon source, aluminate is selected as the aluminum source, the rare earth metal source is a mixture of neodymium chloride and cerium chloride, and the transition metal source is ammonium molybdate. By weight percentage, ZMQ-1 molecular sieve accounts for 60%, the mixture of neodymium and cerium accounts for 12%, ammonium molybdate accounts for 8%, and the binder accounts for 10%.

[0083] Preparation of reaction solution: Add silicon source, aluminum source, rare earth metal source and transition metal source into deionized water according to the above proportions, and adjust the pH value to 11.5.

[0084] Hydrothermal synthesis: The hydrothermal reaction was carried out in an autoclave with the temperature controlled at 210°C and the reaction time being 24 h to obtain ZMQ-1 molecular sieve.

[0085] Catalyst impregnation treatment: The obtained ZMQ-1 molecular sieve is added into a chloride solution of neodymium and cerium, the reaction temperature is controlled at 80°C, and the reaction time is 10 hours, so that the rare earth metal is evenly incorporated into the molecular sieve framework.

[0086] Calcination and phosphorylation: The calcination temperature was set at 600°C for 10 hours in a nitrogen atmosphere. Subsequently, the catalyst was immersed in a 1.0 mol / L phosphoric acid solution for phosphorylation and then dried at 130°C to obtain the final catalyst.

[0087] Summary of Example 3: Based on Example 2, Example 3 further optimizes the types and proportions of rare earth metals and the use of transition metal sources, significantly improving the activity and stability of the catalyst at high temperatures. In particular, the mixed use of neodymium and cerium and the higher calcination temperature make the catalyst more resistant to high temperatures and maintain a high catalytic efficiency during long-term use. Through these technical optimizations, the catalyst of this example shows extremely strong durability and activity in catalytic cracking and long-cycle reactions, and is suitable for a wider range of industrial applications.

[0088] Summary:

[0089] Through the gradual optimization of Example 1, Example 2 and Example 3, different preparation methods and technological innovations based on ZMQ-1 molecular sieve silicon-based rare earth catalysts are demonstrated. From basic catalyst design to optimized high-temperature stability and catalytic performance, this series of embodiments gradually improves the performance of the catalyst. Example 1 provides a feasible solution for the basic preparation of the catalyst, Example 2 further improves the high temperature resistance and stability of the catalyst, and Example 3 improves the durability and catalytic efficiency of the catalyst by optimizing the incorporation of rare earth metals and transition metals. Each embodiment has carried out effective technical expansion on the basis of the previous embodiment, demonstrating a more efficient and stable catalyst formula and superior performance, and providing a more innovative technical solution for the industrial catalytic cracking process.

[0090] Performance test experiment: Catalytic cracking reaction performance test of catalyst

[0091] Purpose:

[0092] This experiment aims to evaluate the performance of ZMQ-1 molecular sieve silicon-based rare earth catalyst in catalytic cracking reaction. By carrying out catalytic cracking reaction on the catalysts prepared in different embodiments, the catalytic activity, cracking conversion rate, product distribution (light oil, medium oil, heavy oil), catalyst selectivity (selectivity for light hydrocarbons), as well as catalyst stability and anti-carbon deposition ability are evaluated, so as to provide data support for catalyst optimization.

[0093] Experimental steps:

[0094] Catalyst preparation:

[0095] According to the experimental design, appropriate amounts of samples were taken from the catalysts prepared in Example 1, Example 2 and Example 3. The catalysts were pretreated with deionized water, washed to remove impurities, and dried until the catalyst quality was stable.

[0096] The catalyst samples were screened to 80-100 mesh size.

[0097] 5 g of catalyst was used in each experiment.

[0098] Reaction equipment settings:

[0099] When using a fixed bed reactor, the temperature, reaction gas flow rate and reaction time in the reactor must be strictly controlled.

[0100] Reaction temperature: The temperature range of 450°C to 550°C was selected to examine the performance of the catalyst under different temperature conditions.

[0101] Feed material: Select light hydrocarbon mixture (such as n-hexane), commonly used raw material petroleum cracking reaction material.

[0102] Feed flow rate: 0.5mL / min, to ensure moderate flow rate and complete reaction.

[0103] Reaction time: set to 30 minutes to observe the performance of the catalyst during the continuous reaction.

[0104] Reaction pressure: normal pressure, simulating conventional industrial reaction conditions.

[0105] Catalyst mass: 5 g of catalyst was used in each experiment to ensure consistency of results.

[0106] Experimental design:

[0107] Experimental group: A group of experiments was set up for each catalyst (Example 1, Example 2, Example 3).

[0108] Control group: The reaction without catalyst was used as the control group to ensure the role of catalyst in the cracking reaction.

[0109] Steps:

[0110] Different catalysts are loaded into the reactor respectively, and the temperature, feed flow rate, reaction time and other conditions are set.

[0111] Start the reactor to react and record reaction parameters such as temperature, pressure, and flow rate.

[0112] Samples were taken periodically during the reaction to analyze the product.

[0113] Catalytic reaction data collection:

[0114] Product collection: After the reaction is completed, various hydrocarbon products in the reaction gas are collected through a condenser. The products are analyzed by gas chromatography (GC) for qualitative and quantitative determination.

[0115] Conversion rate calculation: The cracking conversion rate is calculated by comparing the feed mass and product mass before and after the reaction.

[0116] Product distribution analysis: Use gas chromatography to analyze the mass distribution of C4-C6 (light oil), C7-C12 (medium oil), and C12+ (heavy oil) in the products, and calculate the selectivity of each product.

[0117] Catalyst stability test:

[0118] Acid site analysis: Ammonia adsorption and desorption tests are performed on the catalyst to determine the distribution and acidity of the catalyst’s acid sites. Acid sites are key active sites in catalytic cracking reactions, directly affecting the rate of the catalytic reaction and product distribution.

[0119] Specific surface area test: Use nitrogen adsorption method (BET analysis) to measure the specific surface area and pore structure of the catalyst to understand its surface activity.

[0120] Catalyst anti-carbon deposition ability test:

[0121] Carbon deposition analysis: After the reaction, the catalyst is taken out, properly cleaned and dried, and then the carbon deposition on the catalyst surface is analyzed using thermogravimetric analysis (TGA) or Raman spectroscopy. The amount of carbon deposition directly affects the stability and reaction cycle of the catalyst.

[0122] Data recording and result analysis:

[0123] The conversion rate, product selectivity, catalyst stability and carbon deposition amount of each experimental group were recorded.

[0124] Compare the performance differences of different catalysts under the same conditions and evaluate the advantages and disadvantages of each catalyst.

[0125] Table 1:

[0126]

[0127]

[0128] Results and discussion:

[0129] Catalytic conversion rate:

[0130] The conversion rate of Example 3 is the highest, reaching 78%, indicating that its catalytic effect is the best. This result shows that the synergistic effect of ZMQ-1 molecular sieve and rare earth metals and transition metals greatly improves the catalytic activity.

[0131] In Example 2, the conversion rate is 75%, showing a higher cracking conversion effect.

[0132] The conversion rate of Example 1 is 72%, which is relatively low. This may be because the types or proportions of rare earth metals and transition metals are not as optimized as those of the other two examples.

[0133] Product selectivity:

[0134] The C4-C6 product selectivity of Example 3 is the highest, reaching 65%, indicating that it has a strong ability to generate light hydrocarbons and is an excellent light hydrocarbon selective catalyst. Light hydrocarbon products have high commercial value and can be further converted into important petrochemical products such as ethylene and propylene.

[0135] The C4-C6 selectivity of Example 2 is 60%, which is slightly lower than that of Example 3, but still better than that of other experimental groups.

[0136] The C4-C6 selectivity of Example 1 is 58%, which is slightly lower, indicating that its cracking products tend to be medium and heavy oils.

[0137] Catalyst specific surface area and acid sites:

[0138] The specific surface area of ​​Example 3 is the highest (530 m 2 / g), and the acid content (1.35mmol / g) is also the highest, indicating that it has more catalytic active sites, can provide more active reaction surfaces, and enhance the efficiency of the cracking reaction.

[0139] The specific surface area and acid content of Example 2 and Example 1 are relatively low, but they still have certain catalytic activity and are suitable for cracking reactions.

[0140] Catalyst carbon deposition analysis:

[0141] The carbon deposit amount of Example 3 is the lowest, only 0.7 mg / g, indicating that it has the best anti-carbon deposit performance. This is because its higher acid content and pore structure make it difficult for carbon deposits to deposit during the reaction.

[0142] The carbon deposit amounts of Example 2 and Example 1 are 0.9 mg / g and 1.1 mg / g respectively. Higher carbon deposits may affect the long-term stability of the catalyst.

[0143] Experimental summary: The catalyst of Example 3 exhibits the best catalytic cracking performance, with the highest conversion rate (78%), the best C4-C6 selectivity (65%), a higher specific surface area (530m2 / g), and the lowest carbon deposition (0.7mg / g). This shows that the catalyst has good catalytic performance and long-term stability. Example 2 also shows relatively excellent performance, especially in terms of cracking conversion rate and selectivity, and is suitable for catalytic cracking under medium and high temperature conditions. Although the catalytic performance of Example 1 is not as good as that of Examples 2 and 3, it still has potential value in actual industrial applications, especially under the requirements of low cost and simpler processes.

[0144] In summary, with the optimization of rare earth metals and transition metals and the adjustment of catalyst preparation process, the performance of the catalyst has been significantly improved, especially in terms of light hydrocarbon selectivity and catalyst stability in cracking reactions.

[0145] Comparative experimental design: Performance comparison between silicon-based rare earth catalysts based on ZMQ-1 molecular sieve and traditional catalysts

[0146] Purpose:

[0147] This experiment aims to verify the performance difference between the ZMQ-1 molecular sieve silicon-based rare earth catalyst (the catalyst of the present invention) and the traditional catalyst in the catalytic cracking reaction through comparative experiments, so as to highlight the technical innovation of the present invention. By examining the catalytic conversion rate, product distribution, catalyst stability, carbon deposition and other properties of the catalyst, the advantages of the catalyst of the present invention in catalytic efficiency, stability and long-term effectiveness are demonstrated.

[0148] Experimental design and logic:

[0149] Catalyst selection and experimental group design:

[0150] Experimental Group 1 (catalyst of the present invention): Example 1, Example 2, and Example 3, respectively representing different ZMQ-1 molecular sieve silicon-based rare earth catalysts.

[0151] Control group 1 (traditional catalyst 1): a traditional Y-type molecular sieve catalyst using a conventional aluminate / silicate source and no rare earth metal modification.

[0152] Control group 2 (traditional catalyst 2): traditional MF I type molecular sieve catalyst, modified with conventional acidic medium.

[0153] Control group 3 (conventional catalyst 3): conventional silicon-aluminum catalyst, not metal-modified, with only a binder as an additive.

[0154] Control group 4 (conventional catalyst 4): a conventional bauxite-based catalyst, a common catalyst used for cracking reactions.

[0155] Experimental reaction condition design:

[0156] Temperature: 450℃, 480℃, 500℃, to test the performance of the catalyst at different temperatures.

[0157] Raw materials: light hydrocarbon mixture (such as n-hexane) to ensure consistency with industrial applications.

[0158] Reaction time: 30 minutes, sufficient reaction time to ensure full activity of the catalyst.

[0159] Reactor: Fixed bed reactor to control the stability of reaction conditions.

[0160] Reaction atmosphere: Nitrogen atmosphere is used to ensure the non-oxidizing nature of the reaction.

[0161] Performance evaluation indicators:

[0162] Catalytic conversion rate: the conversion amount of feed material, reflecting the catalytic activity of the catalyst.

[0163] Product selectivity: distribution of cracking products (such as C4-C6 light oil, C7-C12 medium oil, C12+ heavy oil).

[0164] Catalyst stability and carbon deposition: The amount of carbon deposition of the catalyst during the reaction and its stability in multiple reactions are used to evaluate the long-term effectiveness of the catalyst.

[0165] Catalyst acid sites: The number and distribution of catalyst acid sites are determined by ammonia adsorption-desorption method to reflect their effect on cracking reactions.

[0166] Data collection and comparative analysis:

[0167] Data from all experimental groups will include conversion, selectivity, carbon deposition, acid sites, etc., to allow for a comprehensive comparative analysis.

[0168] The performance data of the catalysts are presented in a table, and the performances of different catalysts are comprehensively compared to demonstrate the advantages of the catalysts of the present invention in various indicators.

[0169] Experimental steps:

[0170] Catalyst preparation:

[0171] The catalysts of the present invention (Example 1, Example 2, Example 3) and traditional catalysts (Y-type molecular sieve, MFI-type molecular sieve, silica-alumina catalyst, bauxite catalyst) were prepared respectively according to the preparation method in the claims.

[0172] Catalyst pretreatment:

[0173] All catalyst samples were dried and activated to remove surface impurities and maintain high catalyst activity.

[0174] All catalysts were screened to ensure consistent particle size.

[0175] Reactor preparation:

[0176] The pretreated catalyst samples were loaded into the reactors respectively, and the appropriate reaction temperature and reaction feed flow rate were set.

[0177] The reaction temperatures were set at 450°C, 480°C, and 500°C to ensure stability at each temperature.

[0178] Catalytic cracking reaction:

[0179] The cracking reaction was carried out in the reactor, the reaction time was maintained at 30 minutes, and the conversion rate and product distribution of each group of reactions were recorded.

[0180] The cracking products were analyzed by gas chromatography to determine the mass distribution of components such as C4-C6, C7-C12, and C12+.

[0181] Catalyst post-treatment and analysis:

[0182] The carbon deposition of the catalyst after the reaction is analyzed, the amount of carbon deposition on the catalyst is weighed, and its anti-carbon deposition ability is evaluated.

[0183] The specific surface area and pore volume of the catalyst were determined by BET analysis, and the distribution of its acidic sites was analyzed by ammonia adsorption-desorption method.

[0184] Result recording and analysis:

[0185] The conversion rate, selectivity, acid sites, carbon deposition and other data of each experimental group were recorded for comprehensive analysis.

[0186] The performance difference between the experimental group and the control group was compared to verify the innovation of the catalyst of the present invention.

[0187] Table 2:

[0188]

[0189]

[0190] Experimental summary:

[0191] Catalytic conversion rate:

[0192] The catalysts of the present invention (Examples 1, 2, and 3) show high catalytic conversion rates at all reaction temperatures, especially at higher temperatures (500° C.), where the conversion rate is further improved, indicating that the ZMQ-1 molecular sieve silicon-based rare earth catalyst has a stronger catalytic cracking ability.

[0193] The conversion rates of traditional catalysts (Y-type, MFI-type, silica-alumina, bauxite) are generally low, and the conversion rate improvement at high temperature is limited, indicating that their catalytic activity is weak and cannot meet the needs of efficient catalytic cracking.

[0194] Product selectivity:

[0195] The catalyst of the present invention performs best in the selectivity of C4-C6 light oil, especially Example 3, which has the highest C4-C6 selectivity (50%) at high temperature, proving that it has higher cracking efficiency for light oil.

[0196] The product selectivity of traditional catalysts is poor, especially in the selectivity of medium oil (C7-C12) and heavy oil (C12+), indicating that these catalysts have poor cracking selectivity and cannot effectively crack into light oil preferentially.

[0197] Catalyst stability and carbon deposition:

[0198] The catalyst of Example 3 has the lowest carbon deposition amount, which is only 1.5 mg / g, indicating that it has a strong ability to resist carbon deposition and can maintain good catalytic activity during long-term use.

[0199] The carbon deposit amount of traditional catalysts is generally high, especially the bauxite catalyst (carbon deposit amount is as high as 4.0 mg / g), which shows that its anti-carbon deposition ability is poor and it is easy to deactivate.

[0200] Acidic sites and specific surface area:

[0201] The catalyst of the present invention (Example 3) has a relatively high acidic site (370 μmol / g), which helps to improve the efficiency of the catalytic reaction.

[0202] Traditional catalysts have fewer acidic sites and smaller specific surface areas, which limits their performance in catalytic cracking reactions.

[0203] Summary: This comparative experiment clearly shows the significant advantages of the silicon-based rare earth catalyst based on ZMQ-1 molecular sieve in catalytic cracking. Whether it is catalytic conversion rate, product selectivity, or catalyst stability and anti-carbon deposition ability, the catalyst of Example 3 performs well and is significantly better than traditional catalysts. This proves that the process of the present invention has significant technological innovation in catalytic cracking reactions, can provide more efficient and more stable catalytic performance, and has broad application prospects.

[0204] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. Based on ZMQ-1 molecular sieve silicon-based rare earth catalyst, characterized in that: Calculated by weight percentage, the invention comprises the following components: 60-80% of ZMQ-1 molecular sieve, 5-15% of rare earth metal, 5-10% of transition metal promoter, and 5-10% of binder.

2. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 1, characterized in that: The rare earth metal is selected from yttrium, neodymium, cerium and combinations thereof.

3. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 1, characterized in that: The transition metal promoter is ammonium molybdate, sodium tungstate and a combination thereof.

4. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 1, characterized in that: The crystal structure of the ZMQ-1 molecular sieve is cubic and has a specific surface area of ​​300-600m 2 / g pore structure.

5. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 1, characterized in that: The preparation process of the catalyst is as follows: S1, providing a silicon source, an aluminum source, a rare earth metal source and a transition metal source, and mixing them in the above weight percentage ratio to form a reaction solution; S2, adding a template to the reaction solution, adjusting the pH value to 10-12, and reacting under high pressure hydrothermal conditions to obtain a ZMQ-1 molecular sieve; S3, adding a rare earth metal source to the obtained ZMQ-1 molecular sieve, and reacting at 60-80° C. to uniformly incorporate the rare earth metal into the molecular sieve framework; S4, adding a transition metal source to the reaction solution for impregnation treatment to evenly distribute the transition metal on the surface of the molecular sieve; S5. The catalyst is calcined and phosphorylated.

6. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 5, characterized in that: In the step S1, the silicon source is silicon tetrachloride, the aluminum source is aluminate, the rare earth metal source is rare earth chloride, specifically yttrium, neodymium or cerium chloride, and the transition metal source is ammonium molybdate or sodium tungstate.

7. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 5, characterized in that: The S2 step specifically includes the following steps: S2.1, adding a silicon source and an aluminum source into deionized water, adjusting the pH value of the solution to 10-12, to form a reaction solution; S2.2, add template to the solution and keep stirring; S2.3, transferring the mixed solution to an autoclave, and performing a hydrothermal reaction at 180-200°C for 12-24h to obtain preliminary ZMQ-1 molecular sieve crystals; S2.

4. After the reaction is completed, the template is removed by filtration, and the ZMQ-1 molecular sieve matrix is ​​obtained by washing, and then dried to obtain a preliminary molecular sieve material.

8. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 7, characterized in that: In the step S2.2, the template agent may be CTAB or PEI.

9. The silicon-based rare earth catalyst based on ZMQ-1 molecular sieve according to claim 5, characterized in that: The specific steps of step S5 are as follows: S5.1, the calcination temperature is set to 550-600°C, the calcination time is 6-10h, and the calcination process needs to be carried out under nitrogen or air atmosphere; S5.2, immersing the calcined catalyst in a phosphoric acid solution for phosphorylation; S5.

3. Dry the treated catalyst at 110° C. to obtain the final ZMQ-1 molecular sieve-based silicon-based rare earth catalyst.

10. The ZMQ-1 molecular sieve silicon-based rare earth catalyst according to claim 9, characterized in that: The concentration of the phosphoric acid solution in step S5.2 is 0.1-1.0 mol / L.